IDEOLOGICAL INVOLUTION OF THE ISLAMISTS - Umam, Fawaizul (ULUL ALBAB Jurnal Studi Islam, 2019)
Islamism as one of transnational political Islam ideologies continues to spread throughout the world. Many researchers read the phenomenon of strengthening Islamism solely as part of the Islamic social movements. This article looks at it further as a threat to the social cohesiveness of contemporary society. It intends to describe the Islamism from (1) its genealogy to ideological ideas about the unification of dîn (religion) and dawlah (state) and (2) measuring how relevant that idea is realized in a global and national context and (3) proposing a counter-ideology as a solution. Genealogically, Islamism ideology shows the tendency of revivalism and even fundamentalism, which tries to set Islam as a single system in society life. For contemporary Indonesia concept, the ideology is not only realistic, but is also potentially destructive to the unity, the country-nation awareness, the democracy, and Islam’s mission as raḥmat li al-‘âlamîn. Its deployment can be forestalled by revitalizing an alternative strategic discourse containing Islamic values into every dimension of life in this country. Based on the documentary review, its research findings are expected to enrich the discourse as well as an early warning system for national solidity and religious solidarity, especially in Indonesia.